Pieśń włóczębna dla panny w powieści Floriana Czarnyszewicza Wicik Żywica - Leshkevich, Alena (Slavia Orientalis, 2026)
The article analyses the description of the Easter ritual of visiting homesteads (валачобніцтва in Belarusian) in Florian Czarnyszewicz’s novel Wicik Żywica (1953). Particular attention is paid to a валачобная song dedicated to a maiden (the daughter of the owner of the house visited by the singers) and to the manner of its performance. Florian Czarnyszewicz (1900‑1964) was a Polish writer born in eastern Belarus. According to the plot of the novel, the ritual takes place on Catholic Easter in 1920 near the settlement of Gorka (under this name the author “hid” the current village of Svisloch, Osipovichi district, Mogilev region). In the article, some components of the ritual described by Czarnyszewicz are compared with data from ethnographic sources. These are the following elements: division of the singers into a principal one and the chorus; a song for a maiden with the motif “A young man goes to war and returns to his homeland to marry”; the refrain ‘Zielony sadzik wiśniowy’; improvisation in the lyrics of the song; the wish for a maiden to get married. The analysis showed that in the novel Wicik Żywica, set in eastern Belarus, the author also used ethnographic details from western Belarus, where he lived in the early 1920s.